Virtual Reality Simulation Game for Economics Students: Usability Evaluation - Makeieva, Alona; Kubilinskienė, Svetlana (Vilnius University Open Series, 2025)
This paper presents experiences in the development and usability evaluation of the Erasmus+ project VR-based simulation tools content for developing economics students’ critical thinking, communication, collaboration and creativity skills. The study involved 91 students from 3 countries. The research methodology to determine the relevance of the contentis is based on applying participant method (namely, Event diaries), were Keller‘s ARCS (attention, relevance, confidence, and satisfaction) motivational design model was used as a guiding strategy. In this study content usability: Relevance scored highest (3.64 out of 5), followed by confidence (3.37 out of 5), attention (3.5 out of 5), and content satisfaction (3.04 out of 5).